1984
DOI: 10.2527/jas1984.582423x
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Blood Flow during Early Pregnancy in Ewes: Interaction between the Conceptus and the Ovary Bearing the Corpus Luteum

Abstract: To determine if a transient increase in uterine blood flow (BF) and estradiol-17 beta (E2 beta) secretion occurs during maternal recognition of pregnancy in ewes (as previously observed for sows and cows), 40 nonpregnant (NP) ewes were assigned in equal numbers to surgery on d 9, 11, 13 or 15 postestrus (d 0 = day of estrus). For 20 NP ewes (five/day), each uterine horn (UH) was flushed with saline and uterine flushings (UF) collected. For the remaining 20 ewes, BF was determined for each UH using electromagne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 21 publications
(28 reference statements)
0
14
0
3
Order By: Relevance
“…vascular growth and expression of angiogenic and other factors) in the maternal placenta. The patterns of changes in vascular development parallel those for the expression of several angiogenic and other factors indicating complex regulation of angiogenic processes which regulate uterine and placental blood flow (Reynolds et al 1984, Reynolds & Redmer 1995. Thus, angiogenesis is crucial in developing and building the placental life line between the maternal and fetal systems, and when affected, fetal growth and development are also affected (Carter & Charnock-Jones 2001, Wulff et al 2003, Arroyo & Winn 2008, Fraser & Duncan 2009.…”
Section: Discussionmentioning
confidence: 96%
“…vascular growth and expression of angiogenic and other factors) in the maternal placenta. The patterns of changes in vascular development parallel those for the expression of several angiogenic and other factors indicating complex regulation of angiogenic processes which regulate uterine and placental blood flow (Reynolds et al 1984, Reynolds & Redmer 1995. Thus, angiogenesis is crucial in developing and building the placental life line between the maternal and fetal systems, and when affected, fetal growth and development are also affected (Carter & Charnock-Jones 2001, Wulff et al 2003, Arroyo & Winn 2008, Fraser & Duncan 2009.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, DAVID analysis identified blood circulation and circulatory system process as biological processes affected by day of pregnancy and early P4 treatment. Although angiogenesis has not been well studied during early pregnancy in ruminants, increases in uterine blood flow do occur during early pregnancy in sheep (68).…”
Section: Discussionmentioning
confidence: 99%
“…Placentation that occurs during early pregnancy is one of the most important developmental events (Boshier, 1969;King et al, 1982), since it is tightly associated with embryonic survival (Reynolds and Redmer, 2001). Extensive angiogenesis occurs in both the maternal uterus and fetal placenta during placentation, and umbilical blood flow increases during the same time (Reynolds et al, 1984;Reynolds and Redmer, 1992;. It has been reported that early embryonic mortality increases as placental vascular development decreases (Meegdes et al, 1988;Reynolds and Redmer, 1995).…”
Section: Nutrition Related To Fetal Growth During Late Gestationmentioning
confidence: 99%